2011
DOI: 10.1108/14777831111136090
|View full text |Cite
|
Sign up to set email alerts
|

Motives, difficulties and benefits in implementing the ISO 14001 Environmental Management System

Abstract: PurposeThe purpose of this paper is to examine the motives for implementing the ISO 14001 standard, the difficulties in meeting the standard's requirements and the benefits derived, and to determine the most significant latent constructs (unobserved variables) of these.Design/methodology/approachA research project was carried out in 53 ISO 14001‐certified Greek companies. Exploratory Factor Analyses were applied in order to refine the latent constructs of the ISO 14001 motives, difficulties and benefits.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 32 publications
6
137
1
9
Order By: Relevance
“…Pan [23], exploring the motivations of firms registering ISO 14001 in four far Eastern countries (Japan, Taiwan, Korea, and Hong-Kong), found that the desire for improving corporate image, environmental improvement, gaining marketing advantage, and improving relations with communities were the most important reasons for the ISO 14001 certification. In the same vein, Psomas et al [24], through exploratory factor analysis in Greek companies, emphasized three main sources of ISO 14001 motives: competitive advantage, social requirements, and environmentally-friendly policy. González-Benito, J. and González-Benito, O.…”
Section: Motivesmentioning
confidence: 99%
“…Pan [23], exploring the motivations of firms registering ISO 14001 in four far Eastern countries (Japan, Taiwan, Korea, and Hong-Kong), found that the desire for improving corporate image, environmental improvement, gaining marketing advantage, and improving relations with communities were the most important reasons for the ISO 14001 certification. In the same vein, Psomas et al [24], through exploratory factor analysis in Greek companies, emphasized three main sources of ISO 14001 motives: competitive advantage, social requirements, and environmentally-friendly policy. González-Benito, J. and González-Benito, O.…”
Section: Motivesmentioning
confidence: 99%
“…ISO 14001) were created to help organizations, there are some factors that may prevent a company from successfully implementing those initiatives, out of which the irritation from employees who may oppose the increase in their responsibilities of jobs or lack of commitment of workers is a key factor (Poksinska et al, 2003;Chavan, 2005;Psomas et al, 2011). Therefore these kinds of instance necessitate the recognition and measurement of employee green performance of job to get the commitments of employees.…”
Section: (D) the Level Of Employee Contribution To Implement Cem Initmentioning
confidence: 99%
“…The impacts on firms of the application of ISO 14001 have been deeply investigated by scholars. Recent works concerning benefits of ISO 14001 implementation are [27,[31][32][33][34][35][36][37][38][39][40][41]. Scholars also investigated barriers and constraints to ISO 14001 adoption and maintenance [25,27,30,33,34,37,39,[41][42][43][44][45].…”
Section: Previous Surveys On the Application Of Emas In European Firmsmentioning
confidence: 99%